Risk assessment of achieving greenhouse gas emission reduction target in the maritime industry - Li, Yuwan (2024)
To mitigate climate change, the International Maritime Organization (IMO) has mandated a 50% reduction in shipping-related greenhouse gas emissions by 2050 compared to 2018. While short-term measures are agreed, several barriers remain in achieving this emission reduction target. Existing research only focuses on specific scenarios and ignores comprehensive risks that influence the target realization. Hence, this study fills the research gap by identifying 28 potential risks and prioritizing the most threatening risks using the Political, Economic, Social, Technical, Legal, and Environmental framework. Furthermore, risk assessment on the target achievement is conducted to prioritize risk categories and risk factors via a combination of Evidential Reasoning and Rule-based Bayesian network. Finally, sensitivity analysis is performed to validate the results. The findings show that the categories, in the descending order of their importance, are economic, political, environmental, legal, social, and technological risk. In addition, the results reveal that “high low-carbon fuel prices” is the most pivotal risk under the economic category while notable political, environmental, legal, social, and technological risks are also recognized, each presenting distinct uncertainties in the decarbonization process. This study offers useful insights and strategic recommendations for stakeholders, aiding the transition to low-carbon maritime transportation.